Pengaruh Perendaman Minuman Berkarbonasi terhadap Gaya Elastik pada Elastomerik Ligatur dengan Variasi Panjang Penarikan - Pradipta, Hafidz I.; Wibowo, Budi; Purbaningrum, Diah A,; Prabowo, Yoghi B. (e-GiGi, 2021)
Abstract: Elastomeric ligature is used to fasten orthodontic wires with brackets and can be stretched 1-3 mm as a simulation of bracket in the oral cavity. Its elastic force could decrease caused by salivary pH and water absorption of the elastomeric ligature. Consuming carbonated drinks causes the oral cavity to become acidic which increases the loss of elastic force in the elastomeric ligature with length of stretch variations. This study was aimed to determine the effect of immersion in carbonated drinks on the elastic force of the elastomeric ligature with length of stretch variations. This was an experimental laboratory study with a post-test only control group design. There were a total of 24 samples of American Orthodontic brand elastomeric ligature with royal blue color divided into six groups, consisting of three control groups immersed in artificial saliva, and three treatment groups immersed in carbonated drinks. Each control group and treatment group were given three variations of stretch length, as follows: 1, 2, and 3 mm. The calculation of the elastic force on the elastomeric ligature was performed by using the Universal Testing Machine. Data were analyzed by using the One Way Anova test and LSD post hoc test (p <0.05). The One Way Anova test showed a significant difference in the 1, 2, and 3 mm length of stretch variations for treatment groups. In conclusion, carbonated drinks affect the elastic force of elastomeric ligature with length of stretch variations.Keywords: elastomeric ligature; carbonated drinks; length of stretch variationsÂ Abstrak: Elastomerik ligatur adalah alat yang digunakan untuk mengikatkan kawat ortodonti dengan braket, dapat diregangkan 1-3 mm sebagai simulasi braket dalam rongga mulut. Elastomerik ligatur mengalami penurunan gaya elastik salah satunya disebabkan oleh pH saliva, dan penyerapan air dari elastomerik ligatur. Mengonsumsi minuman berkarbonasi menyebabkan pH saliva menjadi asam sehingga meningkatkan kehilangan gaya elastik pada elastomerik ligatur dengan variasi panjang penarikan. Tujuan penelitian ini untuk mengetahui pengaruh perendaman minuman berkarbonasi terhadap gaya elastik pada elastomerik ligatur dengan variasi panjang penarikan. Desain penelitian ialah eksperimental laboratorium dengan post-test only control group design. Sebanyak 24 sampel elastomerik ligatur merek American Orthodontic dengan warna royal blue, dibagi menjadi enam kelompok, terdiri dari tiga kelompok kontrol perendaman pada saliva buatan, dan tiga kelompok perlakuan perendaman pada minuman berkarbonasi. Setiap kelompok kontrol dan perlakuan diberi tiga variasi panjang penarikan, yaitu penarikan 1, 2, dan 3 mm. Perhitungan gaya elastik pada elastomerik ligatur menggunakan alat Universal Testing Machine. Analisis data menggunakan uji One Way Anova dan uji post hoc LSD pada p<0,05. Hasil uji One Way Anova menunjukkan perbedaan bermakna pada penarikan 1, 2, 3 mm dalam perendaman minuman berkarbonasi. Simpulan penelitian ini ialah terdapat pengaruh perendaman minuman berkarbonasi terhadap gaya elastik pada elastomerik ligatur dengan variasi panjang penarikan.Kata kunci: elastomerik ligatur; minuman berkarbonasi; variasi panjang penarikan